Life-cycle assessment of biochar production systems in tropical rural areas: Comparing flame curtain kilns to other production methods. (June 2017) - Smebye, Andreas Botnen; Sparrevik, Magnus; Schmidt, Hans Peter; Cornelissen, Gerard
Abstract: A life-cycle assessment (LCA) using end point methods was performed for the generation and sequestration of one kg biochar by various pyrolysis methods suitable for rural tropical conditions. Flame curtain kilns, a novel, simple and cost-effective technology of biochar generation, were compared to earth mound non-improved kilns, retort kilns with off-gases combustion, pyrolytic cook-stoves allowing the use of the gas flame for cooking purposes, and iv) gasifiers with electricity production. The impact categories of climate change, particulate matter emissions, land use effects, minerals and fossil fuels were combined to provide the overall impact of biochar generation. In the LCA ranking, earth mound kilns were shown to have negative potential environmental impacts because of their gas and aerosol emissions. Flame curtain kilns had slightly lower potential impact than retort kilns and much lower impact than earth-mound kilns because of the avoidance of start-up wood and low material use and gas emissions. Making biochar from flame curtain kilns was observed to be environmentally neutral in a life-cycle perspective, as the production emissions were compensated for by carbon sequestration. Pyrolytic cook-stoves and gasifiers showed the most positive potential environmental impact in the LCA due to avoided firewood consumption and emissions from electricity generation, respectively. The generation and sequestration of biochar per se by flame curtain kilns was not found to result in direct environmental benefits. Co-benefits in the form of rural applicability, cost-efficiency and agricultural effects due to soil improvement are needed to warrant biochar implementation by this method. Graphical abstract: Highlights: End-point LCA was performed for the generation and sequestration of one kg biochar by various pyrolysis methods. Novel flame curtain kilns were environmentally neutral, as production emissions were compensated for by carbon sequestration. Net environmental benefits can be obtained by co-benefits in the form of positive agricultural effects. Clean stoves and gasifiers were best in the LCA because of avoided deforestation and electricity generation, respectively.